Repeated endoscopic excision of an eroding calcified mesh sling-continued follow-up is required - Tshia-Shu, Lo; Nusee, Zalina (Elsevier, 2010)
The tension-free vaginal tape (TVT) procedure is the most popular worldwide for treating stress urinary incontinence. Intravesical mesh erosion related to the use of the TVT sling is rare. We report a rare case of mesh erosion over the bladder dome, with stone formation developing 11 years after TVT surgery. The diagnosis was made by cystoscopic examination after a 5-month history of lower urinary tract symptoms. Cystoscopic cystolithotomy was performed. No obvious mesh material was seen except for a small filament that was excised cystoscopically. Repeat cystoscopic follow-up was performed a year later. A recurrent stone formation resulted from a nonvisible mesh filament. Repeat cystoscopic cystolithotomy was performed, and the patient refused further surgical intervention. In women with a history of undergoing the TVT procedure and who have persistent lower urinary tract symptoms, a cystoscopic examination is mandatory to avoid delay in diagnosis and underreporting of sling-related complications. Despite satisfactory cystoscopic management, long-term regular follow-up is still required.